The influence of accounting knowledge, business experience, work motivation on the use of accounting information in MSMEs - Metyria Imelda Hutabarat; Loso Judijanto; Rida Ristiyana; Muhamad Syafii; Elis Mediawati (International Journal of Applied Finance and Business Studies, 2023)
This research aims to analyze the effect of accounting knowledge, business experience and work motivation on the use of accounting information. Data collection in this research uses primary data. The population in this research are micro, small and medium enterprises in Medan regency. Sampling obtained 80 business actors, small and medium as the sample in this research. Data analysis in this research uses multiple linear regression analysis with the help of SPSS 26 software. The results of this research partially prove that accounting knowledge and business experience have a positive and significant affect on the use of accounting information, while work motivation positive affect had no significant on the use of accounting information. The results obtained simultaneously are that accounting knowledge, business experience and work motivation have positive significant affect on the use of accounting information.